2015
DOI: 10.1002/path.4516
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal endometriotic lesions associated with cancer are clonal and carry a high mutation burden

Abstract: Endometriosis is a significant risk factor for clear cell and endometrioid ovarian cancers and is often found contiguous with these cancers. Using whole-genome shotgun sequencing of seven clear cell ovarian carcinomas (CCC) and targeted sequencing in synchronous endometriosis, we have investigated how this carcinoma may evolve from endometriosis. In every case we observed multiple tumour-associated somatic mutations in at least one concurrent endometriotic lesion. ARID1A and PIK3CA mutations appeared consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 44 publications
4
113
0
8
Order By: Relevance
“…Additionally, most of the cases that fall within this category are admixed CCC and EC, two histotypes that are largely accepted to arise from the same cell of origin, i.e. glandular epithelial cells of endometriosis (18, 19, 45–48). The mutational data, where informative, indicate that in such cases, the morphologically and molecularly distinct regions have arisen from the same initiation event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, most of the cases that fall within this category are admixed CCC and EC, two histotypes that are largely accepted to arise from the same cell of origin, i.e. glandular epithelial cells of endometriosis (18, 19, 45–48). The mutational data, where informative, indicate that in such cases, the morphologically and molecularly distinct regions have arisen from the same initiation event.…”
Section: Discussionmentioning
confidence: 99%
“…The mutational data, where informative, indicate that in such cases, the morphologically and molecularly distinct regions have arisen from the same initiation event. The sequencing panel employed in this study is limited to hotspot regions of 50 genes and, in cases such as MX2 with only a single CTNNB1 mutation in EC component and no detectable mutations in the CCC, many ancestral mutations, such as ARID1A (48) may have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-genome sequencing of ovarian clear cell carcinomas and endometriotic lesions from multiple patients reveals that there may be multiple classes of endometriosis with a specific high mutational subset serving as the precursor lesion for malignancy. 22 Dr Huntsman also briefly touched on recent work demonstrating cystathionine F-lyase as a novel clear cell carcinoma biomarker. 23 Finally, the mutational profile of HGSOC and the investigation into the site(s) of origin were discussed, and the implication on clinical strategies for risk reducing surgeries again highlighted.…”
Section: The Origins and Early Development Of Ovarian Cancermentioning
confidence: 99%
“…A series of seminal studies have used high-throughput sequencing to profile the intra-tumoral heterogeneity of kidney (Gerlinger et al 2012(Gerlinger et al , 2014Gulati et al 2014), prostate (Boutros et al 2015;Cooper et al 2015;Gundem et al 2015), breast Eirew et al 2015), lung (de Bruin et al 2014;Zhang et al 2014), ovarian (Bashashati et al 2013;Anglesio et al 2015), and other tumors. These studies have universally shown that individual tumors are comprised of myriad cell types present at different frequencies in different spatial sites.…”
Section: Reproducibility Of Analysesmentioning
confidence: 99%